Informática e a educação : o Paraná Digital e o processo de informatização nas escolas públicas do Núcleo Regional de Educação de União da Vitória - Graupmann, Olaf (2014)
The aim of this study was to investigate how information technologies affect the educational process in the schools of the Regional Center of the Education Union Victoria, particularly in the areas of Portuguese and mathematics. In this context, the objective was to also know the changes, the positive aspects and barriers to the implementation of Parana DIGITAL in daily school cited the NRE, and the results presented in IDEB. Thus, to achieve the proposed objectives, the research methodology used was the literature review, a qualitative one, complemented by field research. 17 selected the nine municipalities of the Regional Center of Education Union of Victoria with the aim of quantifying the computer labs installed equipment and technological schools were surveyed. Were also applied two questionnaires, one for teachers and one for students. The questionnaire given to the teachers in the disciplines of mathematics and Portuguese and have focused on characterizing the teachers who teach the Portuguese and mathematics disciplines, as well as access, barriers, training and evaluation of technologies and content of these programs. As for students, a significant sample of ninth graders from elementary to verify access and frequency of use of computer teaching laboratories was performed. They also raised the school's performance in IDEB, SAEB and SAEP to see if there was improvement from implantation From DIGITAL PARANÁ. In conclusion, it is argued that the mere presence of such equipment at school, alone, does not allow the effective and necessary educational transformation and, in specific, to improve the rates and grades of those indicators. It was found that: A) The Paraná Digital proves insufficient to achieve the goals, therefore the percentages found were low and worrying results; B) The schools have a large percentage of use of other media such as television and pendrives. In this context, an obvious situation is that only the availability of computer and internet connection is insufficient to improve school performance. It is understood that it is necessary to rethink the use of computers in the sense that programs and policies, and have a pedagogic proposal using ICT, there specialized laboratory technician support, continued teacher training and, what is more importantly, the monitoring results.